The anti-diabetic effects of metformin are mediated by regulating long non-coding RNA - Wenguang Chang; Wei Li; Peifeng Li (Frontiers Media S.A., 2023)
Type 2 diabetes (T2D) is a metabolic disease with complex etiology and mechanisms. Long non-coding ribonucleic acid (LncRNA) is a novel class of functional long RNA molecules that regulate multiple biological functions through various mechanisms. Studies in the past decade have shown that lncRNAs may play an important role in regulating insulin resistance and the progression of T2D. As a widely used biguanide drug, metformin has been used for glucose lowering effects in clinical practice for more than 60 years. For diabetic therapy, metformin reduces glucose absorption from the intestines, lowers hepatic gluconeogenesis, reduces inflammation, and improves insulin sensitivity. However, despite being widely used as the first-line oral antidiabetic drug, its mechanism of action remains largely elusive. Currently, an increasing number of studies have demonstrated that the anti-diabetic effects of metformin were mediated by the regulation of lncRNAs. Metformin-regulated lncRNAs have been shown to participate in the inhibition of gluconeogenesis, regulation of lipid metabolism, and be anti-inflammatory. Thus, this review focuses on the mechanisms of action of metformin in regulating lncRNAs in diabetes, including pathways altered by metformin via targeting lncRNAs, and the potential targets of metformin through modulation of lncRNAs. Knowledge of the mechanisms of lncRNA modulation by metformin in diabetes will aid the development of new therapeutic drugs for T2D in the future.